2013
DOI: 10.1186/1471-2490-13-37
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated methylation at imprinted genes in prostate tumor tissue detected by methylation microarray

Abstract: BackgroundImprinting is an important epigenetic regulator of gene expression that is often disrupted in cancer. While loss of imprinting (LOI) has been reported for two genes in prostate cancer (IGF2 and TFPI2), disease-related changes in methylation across all imprinted gene regions has not been investigated.MethodsUsing an Illumina Infinium Methylation Assay, we analyzed methylation of 396 CpG sites in the promoter regions of 56 genes in a pooled sample of 12 pairs of prostate tumor and adjacent normal tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…It has been reported that silencing of miR-126 is induced by promoter methylation of its host gene EGFL7 [11]. Hypermethylation of tumor suppressor genes is frequently observed in cancers [13,14], and such epigenetic changes are potential markers for detecting and monitoring tumors [15][16][17]. Aberrantly methylated cancer-related genes contribute to MM progression and its clinical outcome [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that silencing of miR-126 is induced by promoter methylation of its host gene EGFL7 [11]. Hypermethylation of tumor suppressor genes is frequently observed in cancers [13,14], and such epigenetic changes are potential markers for detecting and monitoring tumors [15][16][17]. Aberrantly methylated cancer-related genes contribute to MM progression and its clinical outcome [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Loss of IGF2 and WT1 imprinting in tumors typically results in up regulated expression levels (Brown et al 2008;Jacobs et al 2013), and our recent unpublished findings suggest that IGF2 imprinting may be lost in a subset of patients with DD. As both IGF2 and WT1 expression levels are up regulated in DD cells, we will include WT1 in these ongoing studies to determine if abnormal epigenetic regulation of expression contributes to the increased IGF2 and WT1 transcript levels in this fibrosis.…”
Section: Discussionmentioning
confidence: 71%
“…Presently, there are no data on the methylation status of ARHGEF4, MYOF, WT1, PTAFR, SCYL3, and VPS13D in the literature ( Table 4 ). Nevertheless, ARHGEF4 [ 52 ], [ 53 ] , MYOF [ 54 ], [ 55 ], [ 56 ] , WT1 [ 57 ], [ 58 ] , PTAFR [ 59 ] were upregulated in pancreatic, breast, and prostate cancers.…”
Section: Resultsmentioning
confidence: 99%